Cutaneous adverse events of epidermal growth factor receptor inhibitors: A retrospective review of 99 cases - Kumutnart Chanprapaph (2018)
© 2015 Indian Journal of Dermatology, Venereology, and Leprology. Background: Previous reports regarding the cutaneous adverse events of epidermal growth factor receptor inhibitors are mostly limited to small case reports and case series, mainly involving Caucasian patients. Aims: We describe the trends in the clinical presentation of Asian patients who had cutaneous adverse events induced by epidermal growth factor receptor inhibitors and to explore the relationship between skin adverse events and tumor response. Methods: From 2006 to 2010, medical records of Thai patients with non-small cell lung cancer receiving epidermal growth factor receptor inhibitors were retrieved and analyzed. Results: In all, 99 patients were reviewed and analyzed. Erlotinib and gefitinib were commenced in 75 (75.8%) and 24 (24.2%) patients, respectively. Cutaneous adverse events occurred in 43 (57.3%) patients receiving erlotinib and in 15 (62.5%) patients receiving gefitinib. The most common adverse event was xerosis (52.5%). Less common adverse events included papulo-pustular eruption (27.3%), erythematous maculopapular rash (11.1%), mucositis (6.7%), paronychia (5.1%), and trichomegaly (2%). Elderly patients had a higher occurrence of xerosis. The presence of cutaneous adverse events was significantly higher in subjects who had a tumor response. Limitations: The limitations of study include its retrospective nature, and the initial screening of cutaneous adverse events was done by non-dermatologists. Conclusions: Cutaneous adverse events due to epidermal growth factor receptor inhibitors are not uncommon in the Asian population. We found a positive correlation between the occurrences of cutaneou adverse events and tumor response supporting the view that they are surrogate markers for therapeutic response.